Comprendre les interactions des vendeurs de drogues illicites sur les forums de discussion des cryptomarchés - Paquet-Clouston, Masarah (Canadian journal of criminology and criminal justice, 2018)
This article explores how online drug sellers interact on cryptomarket discussion forums. The results suggest that the sellers' interactions are modulated by their status as sellers. Sellers fuse two roles to adjust their status, combining the role of entrepreneur and the role of volunteer expert. As entrepreneurs, sellers post promotional messages to take advantage of the visibility provided by the forums. They also take on an expert volunteer role, making "effort donations" to the community by helping other participants. These effort donations may be made with the aim of raising their reputation within a community, a key element in the sale of illegal products online. These donations could also be motivated by a form of participatory act, which benefits the maximum number of participants and ensures the welfare and development of the virtual community.